Greening Agriculture: Exploring the Asymmetric Impact of Agriculture on Carbon Emissions in SCO Countries - Usama Abdul Rauf; Amanat Ali; Sareer Ahmad; Nikhil Shil (Journal of Agriculture and Environment for International Development)
The emission of CO2 becomes a main reason for environmental damage. Among various sources, this study aims to focus on the impact of agriculture on CO2 emissions. While agriculture plays a vital role in supplying essential foods, it also contributes to ecological ruin. Using the Nonlinear Panel Autoregressive Distributed Lag (NPARDL) model, the study investigates the nonlinear impacts of agriculture on CO₂ emissions in Shanghai Cooperation Organization (SCO) nations for the period of 1992–2020. The results indicate that negative shocks to agriculture lead to substantial CO₂ emission reductions, in both the short- and long run, whereas shocks that are positive do not show a statistically significant short-run effect but result in statistically significant increase in emissions in the long-run. The study highlights the importance of sustainable agricultural practices and renewable energy consumption in mitigating carbon emissions. By linking these findings to the principles of Green Economics, this research emphasizes the need for policies that balance agricultural productivity with environmental conservation, promoting eco-friendly farming techniques and efficient resource use. The results provide actionable insights for policymakers in SCO countries to achieve sustainable development goals while addressing climate change challenges.